The role of European missions in the Christianization movement in the Ilkhanate state (656-736/1258-1335): بزاڤا مژدەبەرییا مەسیحی دناڤ دەولەتا ئێلخانی دا (٦٥٦-٧٣٦ك/١٢٥٨-١٣٣٥ز) - Mirzo, Falah Kh.; Ismael, Farsat M. (Humanities Journal of University of Zakho, 2024)
After the military failures of the Europeans in their Crusades against the Muslims, the Christianization movement resurfaced in the early 7th century AH/13th century AD. This resurgence took the form of a theory or idea advocated by some European thinkers. This new approach was driven by the need for a different method in the struggle against the Muslims, namely a "peaceful crusade." This was not intended to replace the armed Crusades but to complement them. The Europeans began implementing this idea after the establishment of the Ilkhanate state by Hulagu Khan. This period, spanning the 7th and 8th centuries AH/13th and 14th centuries AD, saw the Ilkhanate rulers, including Hulagu Khan, demonstrate sympathy towards Christians. Taking advantage of this sympathy, the Pope and European kings embarked on missionary activity within the Ilkhanate state. They sent dozens of Franciscan and Dominican missions to achieve their goals, establishing one archdiocese, several bishoprics, and Christian schools. Through these institutions, the Papacy and European monarchs attempted to spread the Catholic doctrine within the Ilkhanate for eighty years of Mongol rule. The research attempts to answer a set of key questions: On what religion or sect did the process of Christianization take place? What was the position of the Mongol Ilkhans and the general population of the state on the Christianization movement? Did Christianization achieve its objectives? The research relies on a detailed analysis of Arabic, English, and Persian sources and references